FLOW CHARACTERISTICS OF INK-JET INKS USED FOR FUNCTIONAL PRINTING - Dimic Misic, Katarina; Karakoc, Alp; Ozkan, Merve; Hashmi, Syed Ghufran; Maloney, Thad; Paltakari, Jouni (Journal of Applied Engineering Science, 2015)
The rheology-related effects of nozzle clogging in inkjet printing can seriously affect ink ejection rate and result in irregular droplet trajectory, resulting in poor printing results. In this study three different inkjet inks, used for functional   printing with a Dimatix materials inkjet printer, are investigated rheologically. In connection with rheological observation a novel method of inkjet trajectory image analysis gives insight into the irregularity of directional deviation due to clogging of nozzles of the printer It is found that the type of solvent used in the ink formulation has an important influence on the rheological behaviour in the printing regime, which directly has an effect on ink-droplet trajectory and contact characteristic with the substrate.
Keywords: Ink droplet trajectory; Nozzle clogging; Rheology of inkjet inks; Inkjet printing